DETECTION OF PRIMARY ANTIBODIES AGAINST SUPERNATANT ANTIGENS IN PIGS VACCINATED WITH INACTIVATED STREPTOCOCCUS SUIS USING DIFFERENT ADJUVANTS - I Putu Heru Darawinata; I Nengah Kerta Besung; I Gusti Ngurah Kade Mahardika (Buletin Veteriner Udayana, 2025)
Streptococcus suis is a pathogenic bacterium that causes disease in pigs and has zoonotic potential, leading to economic losses in the livestock industry and posing risks to human health. This experimental study employed a factorial completely randomized design to evaluate the primary antibody response to supernatant antigens in pigs vaccinated with inactivated Streptococcus suis vaccines formulated with different adjuvants. Twelve pigs were randomly assigned to three treatment groups: a control group (receiving only adjuvant without antigen), a vaccine group with Montanide ISA 201 VG adjuvant, and a vaccine group with Montanide Gel 01 adjuvant. Serum samples were collected weekly for five weeks, and antibody titers were measured using an enzyme-linked immunosorbent assay (ELISA).The results demonstrated that both adjuvanted vaccines significantly increased antibody titers compared to the control group. Antibody production was detectable from the second week post-vaccination, reaching peak levels in the fourth week. Comparative analysis revealed that Montanide ISA 201 VG induced slightly higher antibody responses than Montanide Gel 01. These findings support the use of inactivated Streptococcus suis vaccines with adjuvants as an effective preventive strategy to enhance immunity in swine populations and reduce the risk of zoonotic transmission.